PENGARUH KUALITAS PELAYANAN, PENGETAHUAN PERPAJAKAN, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KANTOR SAMSAT KABUPATEN SUKABUMI - Azizah, Nazma; Riany, Meutia (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
This study aims to determine the effect of service quality, tax knowledge, and tax sanctions on motor vehicle taxpayer compliance. Data collection techniques used in this study were documentation and questionnaires. The sample used in this study was 100 motor vehicle taxpayer vehicles registered at the SAMSAT office in Sukabumi district. The analytical method used is multiple linear regression. From this study, it was found that service quality has a partially significant effect on motor vehicle taxpayer compliance. Tax knowledge has a partial positive effect on motor vehicle taxpayer compliance. Tax sanctions have a partial positive effect on motor vehicle taxpayer compliance.